Die impak van intergeneratiewe trauma. Verkennende perspektiewe tesame met enkele pastorale kantaantekeninge - W. Coetzer (Acta Theologica)
The article focuses on the process of the transmission of trauma within succeeding generations. Typical behaviour and symptoms are highlighted. A summary of typical characteristics of a dysfunctional family is presented, followed by a literature study on the history of research on the theme of intergenerational trauma. Some parallels with a typical dysfunctional home are drawn. The focus then shifts to a pastoral model for counselling family members who suffer from the results of intergenerational trauma. This model is based mainly on four therapeutic models presented in the literature regarding the counselling of victims of intergenerational trauma and dysfunctional families.